MAKNA DAN FUNGSI ULOS DALAM ADAT MASYARAKAT BATAK TOBA DI DESA TALANG MANDI KECAMATAN MANDAU KABUPATEN BENGKALIS - Candra Agustina; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Ulos was the result of Batak women weaving. Ulos was used in any traditional ceremony at Batak Batak Toba community in particular. The process of granting ulos (mangulosi) on the Toba Batak society this will be done in accordance with the Natolu Dalihan system has a very important role in any ceremony either in the Marriage ceremony, the ceremony of death, Seven months, entering the new home. Ulos types most often used in any traditional ceremony as in (a) marriage ceremony is as follows: Panssamot, Ulos Holong, Ulos Sadum, (b) Ulos in death rituals: Ulos Tujung Ulos and Dielectric, Ulos Ragihotang, Ulos Sampetua and Ulos Holong (c) Ulos used in ceremony of Entering the new home: Ulos Sampetua Ulos (d) used in the traditional ceremony of seven Monthly is Ulos Mulagabe and Ulos Maratur.Toba Batak society Ulos has a meaning and a very important function, Any custom event Batak Toba surely they would use Ulos. The granting of this phrase conveys a sense of Ulos affection from parents to their children. In the traditional ceremony of marriage and the death of Toba Batak communities in the process of granting this Ulos (mangulosi) are always followed by a musical accompaniment (gondang). Batak Toba Ulos on has a different Meaning in each condition or in a custom what Ulos will be used. Ulos a result Batak Toba woven this has value, so this became one of ulos living extra for craftsmen or weavers Ulos that want to help finance his family as well as adding to the income of the husband. Granting of Ulos in a traditional ceremony of marriage and death of this Ceremony will be accompanied by the music, which is where the music will be adjusted to the condition or State of the traditional ceremony which is being run by Batak Tobasociety.Keywords: Ulos, batak Tobaculture, and society of Toba